S8.1 Lessons learnt from global HIV drug resistance initiative: implications for MDR-GC. (10th July 2011) - Sutherland, D
Abstract : The WHO, in collaboration with the Bill and Melinda Gates Foundation and the International AIDS Society developed the Global HIV Drug Resistance Network. It is comprised of a network of countries and accredited laboratories. The Network serves as an advisory and evaluation function to the WHO HIV drug resistance team and countries implementing the strategy. Surveillance of HIV drug resistance is critical because it helps to detect the circulation of resistance strains and directs measures to preserve programme effectiveness. This presentation will explore how lessons learnt from the HIV drug resistance initiative could be applied to slow the spread of MDR-GC.